Faktor-Faktor yang Mempengaruhi Persepsi Milenial Sebagai Viewer terhadap YouTuber Gaming di Batam - Wahyu Hati, Shinta; Mallouhi El Arisni, Shafira (Bahtera Inovasi, 2023)
The aim of this research is to identify and analyze the factors that influence the perception of the millennial generation as YouTuber gaming viewers in Batam. The technique used to collect data is a questionnaire. The data analysis method used in this research is confirmatory factor analysis (CFA). The results of the research show that from the 14 indicators analyzed, 4 new factors were formed, namely: impact on viewers, content sharing, audience perceptions of YouTuber videos, and benefits received. After analysis, the most dominant factor influencing the perception of the millennial generation as viewers towards gaming YouTubers in Batam is the impact on viewers, with a variance value of 22.169%.